Relaxation and exchange dynamics of hyperpolarized 129Xe in human blood. Issue 2 (28th August 2014) - Norquay, Graham; Leung, General; Stewart, Neil J.; Tozer, Gillian M.; Wolber, Jan; Wild, Jim M.
<x xml:space="preserve">Abstract</x> Purpose 129Xe‐blood NMR was performed over the full blood oxygenation range to evaluate 129Xe relaxation and exchange dynamics in human blood. Methods Hyperpolarized 129Xe was equilibrated with blood and isolated plasma, and NMR was performed at 1.5 T. Results The 129Xe relaxation rate was found to increase nonlinearly with decreasing blood oxygenation. Three constants were extrapolated: <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj23trfsg4" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />rsO2</alternatives> = 11.1, a "relaxivity index" characterizing the rate of change of 129Xe relaxation as a function of blood oxygenation, and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj23trfsfk" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />1/T1oHb</alternatives> = 0.13 s−1 and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj23trfsks" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />1/T1dHb</alternatives> = 0.42 s−1, the 129Xe relaxation rates in oxygenated blood and deoxygenated blood, respectively. In addition, rate constants, <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj23trfshp" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />ka = </alternatives> 0.022 ms−1 and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj23trfs8t" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />kb</alternatives> = 0.062 ms−1, were determined for xenon diffusing between red blood cells (RBCs) and plasma (hematocrit = 48%). The 129Xe‐O2 relaxivity in plasma, <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj23trfs4m" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />rO2</alternatives> = 0.075 s−1 mM−1, and the 129Xe relaxation rate in isolated plasma (without dissolved O2), <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj23trfsd1" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />1/T1, b0</alternatives> = 0.046 s−1, were also calculated. Finally, intrinsic 129Xe‐RBC relaxation rates, <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj23trfsbx" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />1/T1, aoHb</alternatives> = 0.19 s−1 and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj23trfs32" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />1/T1, adHb</alternatives> = 0.84 s−1, in oxygenated blood and deoxygenated blood, respectively, were calculated. Conclusion The relaxation and exchange analysis performed in this study should provide a sound experimental basis upon which to design future MR experiments for dissolved xenon transport from the lungs to distal tissues. Magn Reson Med 74:303–311, 2015. © 2014 Wiley Periodicals, Inc.